Total Demand, Use and Unmet Need for Modern Contraceptives Among Women Living in Informal Settlements in Kira Municipality, Wakiso District, Uganda. Implications for Urban Health - Tetui, Moses; Baroudi, Mazen; Ssekamatte, Tonny; Birabwa, Catherine; Kibira, Simon Peter; Atuyambe, Lynn; Delamou, Alexandre; Makumbi, Fredrick Edward (Frontiers in Global Women's Health, 2021)
Introduction Uptake and utilization of modern contraceptives has public health benefits-reduction in abortions, unintended pregnancies and consequently maternal mortality. However, paucity of evidence on key indicators of family planning in the informal settlements abounds. Data are usually collapsed within the larger urban communities that tend to mask peculiarities of informal settlements. This study determined the proportion of women using modern contraceptive, the unmet need for modern contraceptives and the total demand in informal settlements of an urban municipality. Methods A cross-sectional study conducted among 626 in the reproductive age (15-49 years) in the informal settlements of Kira municipality. Multi-stage sampling was applied in the selection of the respondents. Descriptive and a log-binomial regression analysis was conducted to determine percentage of women using modern contraceptives, unmet need and total demand with their associated factors. All analyses were conducted using STATA version 15.0. Results The total demand for contraceptives was 84.9%, modern contraceptive prevalence was 47.4% and the unmet need was 37.3%. The total demand for contraceptives was associated with women’s education status (PR 0.87, 95% CI: 0.80-0.94), number of living children (PR 1.49, 95% CI: 1.24-1.79) and the woman’s fertility preference (PR 0.90, 95% CI: 0.84-0.97). Prevalence of modern contraceptive use was associated with age (PR 1.35, 95% CI: 1.07-1.69), women’s education status (PR 0.73, 95% CI: 0.53-0.99), number of living children (PR 1.74, 95% CI: 1.15-2.63), fertility preference (PR 0.48, 95% CI: 0.30-0.77) and the woman’s decision-making power (PR 1.45, 95% CI: 1.18-1.78). The unmet need for modern contraceptives was associated with age (PR 0.68, 95% CI:0.48-0.97), number of living children (PR 1.40, 95% CI: 1.01-1.93), fertility preference (PR 1.70, 95% CI:1.24-2.34) and the woman’s decision-making power (PR 0.64, 95% CI:0.50-0.81). Conclusions Less than half of the women in reproductive age in the selected informal settlements were users of a modern contraceptives, the unmet need in the informal settlements of Kira municipality was high. Results indicated the need to take into consideration the education status, number of living children, women’s fertility preferences and the woman’s empowerment status when designing Interventions. Development of Interventions need to critically consider a systems lens.